2018
DOI: 10.1016/j.ijid.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of a single dose of a live attenuated Japanese encephalitis chimeric virus vaccine in Vietnam: A single-arm, single-center study

Abstract: A single dose of JE-CV in children and adults aged 9 months to 60 years in Vietnam elicited a protective immune response and was well tolerated with no safety concerns. Registered at www.clinicaltrials.gov (NCT02492165).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…No new safety issues were identified. Solicited adverse reactions following vaccination were most frequently reported in the 12 to < 24 months age group, consistent with a previous clinical study that assessed single dose of JE-CV in both children and adults [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…No new safety issues were identified. Solicited adverse reactions following vaccination were most frequently reported in the 12 to < 24 months age group, consistent with a previous clinical study that assessed single dose of JE-CV in both children and adults [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our post-marketing, observational, active safety surveillance study supports the good safety profile of JE-CV when administered under reallife use in South Korea. The safety profile of JE-CV described here is consistent with that reported in previous clinical studies in children and adults [8][9][10][11][12][13] and a large phase IV, postlicensure, safety study in children [14]. No new safety issues were identified.…”
Section: Discussionsupporting
confidence: 87%
“…For humans, two viral-vector vaccines are available: Imojev, a Japanese encephalitic virus (JEV) vaccine; and Dengvaxia, a Dengue vaccine (both from Sanofi Pasteur). Both are produced using the chimeric YFV as vector: two of the YFV genes have been replaced by genes encoding the pre-membrane (prM) and the envelope (E) protein of JEV or DENV, and the chimeric viruses are propagated in cell culture (83,84). Conversely, several viral vector vaccines have been licensed for veterinary use because of the less stringent regulatory requirements (76).…”
Section: Viral-vector Vaccinesmentioning
confidence: 99%
“…59,60 Moreover, clinical studies and post-marketing surveillance all showed favorable safety profile of JE-CV (Table 1). [61][62][63][64][65][66][67][68] The most common adverse effects were injection site reaction with incidence of 6.3% to 37.8% and fever (3.6%-39.0%). Solicited adverse reactions following vaccination were most frequently reported in children younger than 24 months of age.…”
Section: Live-attenuated Chimeric Je Vaccinementioning
confidence: 99%
“…Solicited adverse reactions following vaccination were most frequently reported in children younger than 24 months of age. 63 , 68 Few serious adverse reactions had been reported, but further investigations showed unrelatedness to JE–CV vaccination.…”
Section: Safety Of Japanese Encephalitis Vaccinesmentioning
confidence: 99%